SISTEM INFORMASI PENJUALAN MATERIAL PADA TOKO BANGUNAN IWAN JAYA BERBASIS DESKTOP: Sales;Building Materials;Data Flow Diagram;Tools;Visual Basic Net. - Huda Aminuddin, Fattachul; Andini, Riska (FORTECH (Journal of Information Technology), 2021)
Sales of building materials at Toko Iwan Jaya is one of the entrepreneurs engaged in the sale of building materials that still uses a manual system. One of them is the building material sales information system at Toko Iwan Jaya, which is not yet computerized and well-integrated, so it still has many shortcomings in dealing with sales problems. To design a new system, the tools used are Data Flow Diagram (DFD) Modeling with Visual Basic Net applications so that it can facilitate the process of communication and coordination with customers in order to achieve maximum results as expected by customers. This research has produced a Building Material Sales Information System at the Desktop-Based Iwan Jaya Building Store.